Pemanfaatan Teknologi Interaktif dalam Mengurangi Dampak Brain Rot pada Siswa - Abdul Aziz, Nurdin (CV RIFAINSTITUT, 2025)
The phenomenon of brain rot in students, characterized by a decline in focus, concentration, and memory due to excessive exposure to fast-paced content, has become an increasing challenge in modern education. Interactive technology is considered an effective solution to mitigate these negative effects. This article aims to explore the use of interactive technology in reducing the impact of brain rot on students. Through an approach based on the use of digital tools that support active learning, this paper identifies various technological strategies that can be applied to enhance cognitive engagement, such as game-based learning, virtual reality (VR)-based learning applications, and online collaborative platforms. The study also discusses the role of teachers and educational institutions in designing curricula that optimally integrate interactive technology to mitigate brain rot and improve the quality of learning. The expected outcomes from the application of interactive technology are enhanced cognitive abilities in students to cope with the demands of more complex learning and a reduction in memory decline caused by the disruption of fast-paced content.